Impactos socioambientais e desempenho da fossa verde no Assentamento 25 de Maio, Madalena (Ceará) - Coelho, Christine Farias (2013)
The contamination of aquatic ecosystems through discharge of waste is one of the environmental impacts more often observed in the Brazilian Northeast semiarid environment, resulting in losses of the multiple uses of water and of collective health. The planned water reuse assumes a fundamental role in the sustainable management of water resources. This study aims to evaluate the performance and environmental impacts of the green sewage modules technology (GSM) implanted in "25 de Maio" land reform Settlement, (Madalena, Ceará). This social technology corresponds to an alternative model of treatment of household wastewater that considers water reuse in productive backyards, protection of natural resources and contributes to rural sanitation. The research adopted the case study of 58 GSM that were constructed using a participative approach. The level of satisfaction and ownership of technology was achieved through the combined technique of participant observation and interviews conducted from September 2011 to September 2012. The GSM were monitored at the same time the interviews were carried out and the following assessment criteria: degree of use, cultivation and plant diversity, placement of seedlings, seedling size and quantity, occurrence of overflow, reflux, obstruction, odour and conducting maintenance. Regarding the level of satisfaction, it is noted that contentment with GSM is most visible where the banana trees produce fruits and at situations of satisfactory performance of the system. Water scarcity affected the performance of some GSM due to the lower contribution of effluent coming from domestic water consumption. Overall the use of productive backyards associated with ecological sanitation strengthens family farms and appreciates the local culture also promotes environmental health. The assessment quality of GSM substrate was based on microbiological (SMB-C, SBR and qCO2) and chemical (pH, P, OM, EC) parameters analyzed in samples from five beds chosen under different managements systems. The results showed that systems with higher metabolic activity are those where we observe the best scenarios for crops development. The satisfactory development of crops, including production of fruits (papaya, banana, peppers and tomatoes) may be associated with the cultivation of multiple species on beds, suggesting an array of crops that best fits the levels phosphorus,nitrogen, and especially content salinity, found in substrates collected. Representative samples of tomato (Solanum esculentum), pepper (Capsicum chinense), banana (Musa sp.) and malvarisco leaves (Plectranthus amboinicus L.) were subjected to analysis of sanitary quality, and the results indicated that they are fully able to consumption. The GSM design parameters were calculated using the mass balance of water that include estimate of per capita consumption of water, sewage contribution and coefficient of return (r) in two different situations: household with piped water and house devoid of piped water. In order to estimate the consumptive use of GSM, it was used a control bed cultivated with banana (Musa spp.), in which the rate of crop evapotranspiration (Etc), verified by the methods Class A pan and Penman-Monteith, showed a water consumption 5,1 mm.day-1. The satisfactory design of GSM for the use most efficient of water effluent from domestic sewage is 30 m² for households with piped water and 2 m² for households devoid of piped water. It emphasizes the perspective of public policy formulation sanitation for rural land reform projects with a view to healthy housing and the promotion of health.